Eksplorasi Makna Sosial SAK EMKM Oleh Pelaku UMKM Kabupaten Gresik Melalui Teori Konstruktivisme - Sentosa, Yelsa Yunianti; Rachmi, Nur Habiba (Journal of Economics, Business, Accounting and Management, 2025)
This study aims to explore the social construction of meaning of the Financial Accounting Standards for Micro, Small, and Medium-sized Entities (SAK-EMKM) among MSME actors in Gresik Regency using a social constructivist approach. Rather than focusing on the technical implementation of SAK-EMKM, this research examines how business owners perceive and interpret the standard based on their experiences, social interactions, and cultural context in daily bookkeeping practices. A descriptive qualitative method was employed, using semi-structured interviews, non-participatory observation, and documentation involving five purposively selected informants who are members of HIPMI Gresik. Data were analyzed thematically based on Berger and Luckmann’s three constructivist processes: externalization, objectivation, and internalization. The findings reveal that understanding of SAK-EMKM is still limited, and financial recording is carried out in simple forms based on practical needs, hereditary habits, and social environmental influences. Accounting meanings are shaped through social interaction and collective experience rather than formal education. Therefore, internalization of SAK-EMKM requires support from social ecosystems such as business communities, mentoring, and contextual communication to make it more acceptable and applicable among MSME actors.